PENGARUH MODEL PEMBELAJARAN DAN KEMAMPUAN AWAL TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERPIKIR TINGKAT TINGGI - Setiawan, Nur Candra Eka (FKIP Universitas Wisnuwardhana, 2017)
Teachers in SMAN 1 Turen had tried to apply innovative learning models but some problems occurred in the implementation. The improvement of learning quality which emphasized on learning process could be done by giving students scientific experience. The scientific experience which was implemented in Hypothetical-Deductive Learning Cycle (HDLC), Student Teams Achievement Divisions (STAD) and Direct Instruction method (DI) was expected to be able to improve the students’ achievement and higher order thinking skills. This research aimed to know the difference of the effect of using HDLC, STAD and DI based on prior knowledge on the chemical equilibrium toward achievement and high ordered thinking skill of XI IPA SMAN 1 Turen students. This research used a quasi experiment design with factorial design: 3x2. The research was performed in SMAN 1 Turen, research sample were chosen using cluster random sampling technique, consist of 3 classes, which are XI IPA 2 class (36 students) using HDLC, XI IPA 3 class (36 students) using STAD and XI IPA 4 class using MPL. The Instrument validity and reliability test showed that 30 questions were valid with content validity of 95,3% and the reliability of 0,917. Data was analyzed using program Statistical Package for Social Sciences 16.0 version for windows on significance degree a(alpha)= 0,05 with ANOVA test. The research showed that (1) There was a difference on students’ achievement and high order thinking skills of science XI SMAN 1 Turen students using HDLC, STAD and DI on the chemical equilibrium; (2) There was a difference on students’ achievement and high order thinking skills of science XI SMAN 1 Turen students with high and low level of prior knowledge on the chemical equilibrium; (3) There was a difference of students’ achievement and high ordered thinking skill using HDLC, STAD and DI with different prior knowledge.Keywords: learning models, prior knowledge, chemistry achievement, high order thinking skills